Coronary lipid-rich plaque characteristics with acute coronary syndrome and chronic coronary syndrome: a near infrared spectroscopy and intravascular ultrasound study. (14th October 2021) - Takahashi, N; Dohi, T; Endo, H; Nishio, R; Fukase, T; Takeuchi, M; Doi, S; Kato, Y; Okai, I; Iwata, H; Okazaki, S; Isoda, K; et al.
Abstract: Background: Asians have a much lower incidence of adverse coronary events than Caucasians, and the characteristics of vulnerable plaque might be different among the ethnics. Purpose: The aim of this study was to investigate the clinical characteristics of lipid-rich plaque (LRP) in the Asian population and we also aimed to distinguish the characteristics of an acute coronary syndrome (ACS) culprit lesion and a chronic coronary syndrome (CCS) culprit lesion. Furthermore, we evaluated the association between lipid core burden index (LCBI) and cardiovascular risk factors, lipid profiles, and inflammatory biomarkers, as determined in vivo by near infrared spectroscopy intravascular ultrasound (NIRS-IVUS) imaging in patients undergoing percutaneous coronary intervention (PCI). Methods: We evaluated 207 patients (ACS, n=75; CCS, n=132) who underwent PCI under NIRS-IVUS. Plaque characteristics and the extent of LRP [defined as a long segment with a 4-mm maximum LCBI (maxLCBI4mm)] on NIRS in de-novo culprit and non-culprit segments were analyzed. Results: The mean age was 65 years old and 82% of patients were male. The ACS culprit lesions had a significantly higher maxLCBI4mm (median [interquartile range (IQR)]: 533 [385–745] vs. 361 [174–527], p<0.001) than the CCS culprit lesions. Whereas, no significant difference was seen in maxLCBI4mm between ACS and CCS non-culprit lesion segments (246 [53, 342] vs. 185 [37, 350], p=0.47) (Figure 1). Receiver-operating characteristic analysis showed that the NIRS maxLCBI4mm could distinguish the ACS culprit segment from the CCS culprit segment, with a sensitivity of 73% and a specificity of 69% (c-statistic = 0.69; p<0.001, cut-off value of max LCBI4mm = 408) (Figure 2). On multivariate logistic analysis, a large LRP (defined as maxLCBI4mm ≥400) was the strongest independent predictor of the ACS culprit segment (odds ratio, 3.87; 95% confidence interval, 1.95–8.02). In non-culprit segments, 19.8% of patients had at least one large LRP without a small lumen. No significant correlation was found between the extent of LRP and circulating lipid profiles and inflammatory makers biomarkers (hs-CRP, IL-6, TNF-α) in both the culprit and non-culprit lesion segments, whereas the extent of LRP was positively correlated with IVUS plaque burden (r=0.24, p<0.001). Conclusions: We confirmed that NIRS-IVUS plaque assessment could be useful to differentiate ACS from CCS culprit lesions, and that a threshold maxLCBI4mm ≥400 was clinically suitable in Japanese patients. No systemic surrogate markers were found to be associated with the extent of LRP by NIRS in culprit and non-culprit segments. Consequently, we believe that direct intravascular evaluation of coronary plaque characteristics remains important for identification of high-risk LRP. Funding Acknowledgement: Type of funding sources: None.